WHEN GOOGLE SEARCH ENGINE TALKS TO: CORPUS-BASED TRANSLATION (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
Language development within linguistics rapidly grows and affects the most, particularly in translation studies. The influence has mapped the interest of a lot researcher in Indonesia, due to research method development based on corpus linguistics facilitates the expansion of translation studies scope and address new perspectives to translation raters. Corpus-based translation of this study comes to employ lexicon from statistical tools. The data collection is health protocolary text from several domestic and overseas media where record a large and structured set of texts. The applied method is qualitative research integrated with a corpus-based as descriptive approach and the analysis tool is Google Search Engine patterned by content analysis. Therefore, this study examines translation accuracy and acceptability of English terms as source language toward their Indonesian terms as target language that available online media and the quantity appearance about the COVID-19. This elaboration assessment well creates quality among them to rate how extent the lexicon reaches numerical form.